The Baryonic Content of Galaxies Mapped by MaNGA and the Gas Around Them - Viacheslav V. Klimenko; Varsha Kulkarni; David A. Wake; Suraj Poudel; Matthew A. Bershady; Celine Péroux; Britt Lundgren (The Astrophysical Journal, 2023)
We analyze the cool gas in and around 14 nearby galaxies (at z < 0.1) mapped with the Sloan Digital Sky Survey IV MaNGA survey by measuring absorption lines produced by gas in spectra of background quasars/active galactic nuclei at impact parameters of 0–25 effective radii from the galactic centers. Using Hubble Space Telescope/Cosmic Origins Spectrograph, we detect absorption at the galactic redshift and measure or constrain column densities of neutral (H i , N i , O i , and Ar i ), low-ionization (Si ii , S ii , C ii , N ii , and Fe ii ), and high-ionization (Si iii , Fe iii , N v , and O vi ) species for 11 galaxies. We derive the ionization parameter and ionization-corrected metallicity using cloudy photoionization models. The H i column density ranges from ∼10 ^13 to ∼10 ^20 cm ^−2 and decreases with impact parameter for r ≳ R _e . Galaxies with higher stellar mass have weaker H i absorption. Comparing absorption velocities with MaNGA radial velocity maps of ionized gas line emissions in galactic disks, we find that the neutral gas seen in absorption corotates with the disk out to ∼10 R _e . Sight lines with lower elevation angles show lower metallicities, consistent with the metallicity gradient in the disk derived from MaNGA maps. Higher-elevation angle sight lines show higher ionization, lower H i column density, supersolar metallicity, and velocities consistent with the direction of galactic outflow. Our data offer the first detailed comparisons of circumgalactic medium (CGM) properties (kinematics and metallicity) with extrapolations of detailed galaxy maps from integral field spectroscopy; similar studies for larger samples are needed to more fully understand how galaxies interact with their CGM.